ARCHITECTURE AS SOURCE OF INSPIRATION FOR DEVELOPMENT OF AUTHOR’S COLLECTIONS OF CLOTHING - Васильєва, О. С.; Винничук, М. С.; Васильєва, І. В.; Олійник, І. В. (Art and Design, 2020)
Identify the features of the artistic and plastic properties of gothic and neo-gothic architecture. Find their characteristic forms and artistic and compositional features, explore and highlight the characteristic stylistic interpretations of gothic architecture in modern clothing collections. The study used the basic principles of a systematic approach to the art design of modern author’s clothing collections: literary and analytical studies and figuratively associative stylization of the source of creativity. The analysis carried out and the most characteristic artistic and compositional solutions of the gothic architectural style solutions. The basic techniques and stylization of the elements of the gothic architectural style in modern collections of fashionable clothes are determined. The principles of design modern collections of fashion designers are defined, where a gothic architectural style was used as a creative source. The research results used in the development of the author’s collection of women’s clothing. The paper sets out the basic artistic and compositional features of the gothic and neo-gothic architectural styles (forms, decorative elements and color combinations) and their application in the design of collections of modern fashionable clothes. The analysis of the artistic and compositional features of the collections of the world’s leading designers in the gothic and neo-gothic styles carried out and information about the features of their interpretation systematized. Practical recommendations on the choice artistic and compositional solutions, design and decorative elements, selection of materials, color, accessories, hats, for the design of modern women’s clothing with stylization elements of gothic and neo-gothic architectural styles are presented. The research results used to develop a collection of women’s clothing.